Synthesis and Characterization of Porous Polymer as a Support Matrix for Lipase Immobilization - Erwanto, Erwanto; Saputra, Arya Ananda; Abimanyu, Muhammad Rakha (Hydrogen: Jurnal Kependidikan Kimia, 2025)
Immobilization of lipase on solid supports has become a promising approach to improve enzyme stability, activity, and reusability in various industrial processes. This study focuses on the development of a porous polymer, poly(glycidyl methacrylate-co-trimethylolpropane trimethacrylate) [Poly(GM-co-TT)], as a functional support for covalent lipase immobilization. The experimental procedure included three main stages. First, Poly(GM-co-TT) was synthesized via free radical polymerization using a ternary porogenic solvent system consisting of 1,4-butanediol, 1-propanol, and water in a 4:7:1 (v/v) ratio to obtain a porous structure. Second, lipase was immobilized covalently through the reaction between epoxy groups of the polymer and amino groups of the enzyme, using a 0.2 M KCl–NaOH buffer (pH 11) at a final enzyme concentration of 10 mg/mL, incubated at room temperature for 120 minutes. Third, characterization was performed using FTIR spectroscopy and scanning electron microscopy (SEM) to verify successful immobilization. FTIR analysis revealed the presence of ester (C=O), ether (C–O–C), and epoxide (C–O) groups in the polymer. Post-immobilization spectra showed reduced epoxy band intensity (~910 and 840 cm⁻¹) and the appearance of amide bands (~1640–1660 cm⁻¹), indicating covalent bonding between polymer and enzyme. SEM images confirmed a porous, globular, interconnected morphology with well-distributed pores, ideal for enzyme anchoring. The open and rough surface increases surface area, enhancing immobilization efficiency. The novelty of this study lies in employing Poly(GM-co-TT) as a porous polymer that preserves epoxy functionality while effectively supporting covalent lipase immobilization.